Right ventricle remodeling after transcatheter tricuspid leaflet repair in patients with functional tricuspid regurgitation: Lessons from the surgical experience - Albertini, Alberto; Nerla, Roberto; Castriota, Fausto; Squeri, Angelo (Frontiers in Cardiovascular Medicine, 2022)
Clinically significant tricuspid regurgitation (TR) is common and associated with excess mortality. At the same time right ventricular (RV) failure is a complex clinical syndrome that results from many causes, but is often associated with long-term prognosis. Whilst results of isolated tricuspid valve (TV) surgery are often unsatisfactory and limited by the prohibitive risk of most patients, the recent development of percutaneous recovery techniques has opened new scenarios. In consideration of the complexity of the mechanisms that lead to right heart failure and RV dysfunction it is important to understand the real advantages that percutaneous TV treatment can offer, more specifically the effect of TR reduction on RV remodeling in the setting of functional tricuspid regurgitation (fTR).